1959
DOI: 10.1007/bf02641143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of composition and polymorphic form on the hardness of fats

Abstract: Summary Hardness is an important index in the performance of confectionery and other fats. Using an instrument and technique which were essentially a modification of those used in the Brinell test as applied to metals, the effect of composition and polymorphic form on the hardness of fats was investigated. It was found that the hardness of a given sample of fat was influenced by the degree of tempering to which the sample had been subjected. Hardness always increased as the components of a fat were converted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1960
1960
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…An increase in crystal size seems to cause a decrease in the hardness index of fats (Feuge and Guice 1959). Viscoelastic testing showed that the shear modulus of a plastic fat was inversely proportional to the third power of the particle diameter (Shama and Sherman 1968).…”
Section: Treatments During Manufacturingmentioning
confidence: 98%
See 1 more Smart Citation
“…An increase in crystal size seems to cause a decrease in the hardness index of fats (Feuge and Guice 1959). Viscoelastic testing showed that the shear modulus of a plastic fat was inversely proportional to the third power of the particle diameter (Shama and Sherman 1968).…”
Section: Treatments During Manufacturingmentioning
confidence: 98%
“…Rapid cooling leads to smaller crystals and higher solid fat contents, 2 factors which lead to an increase in butter hardness (deMan 1963b; Parkinson and others 1970;Sone and others 1966). An increase in crystal size seems to cause a decrease in the hardness index of fats (Feuge and Guice 1959). Viscoelastic testing showed that the shear modulus of a plastic fat was inversely proportional to the third power of the particle diameter (Shama and Sherman 1968).…”
Section: Treatments During Manufacturingmentioning
confidence: 99%
“…Bourne and Comstock (1986) reported that FTC values varied from −0.02 to −1.97 for thermally processed fruits and vegetables. The firmness of fats (Feuge and Guice 1959), beeswax (Miyada and Tappel 1956), frankfurters (Simon et al. 1965), cooked beef (Capraso et al.…”
Section: Resultsmentioning
confidence: 99%
“…Cocoa butter or chocolate which has been heated to well above the melting point of the fat and then quickly solidified in the alpha form will undergo changes in crystal structure for weeks when held at room temperature (9). 0a the other hand, it has been stated (10) that when properly tempered chocolate is cooled after molding or enrobing, the cocoa butter solidifies initially in the beta prime form but the transformation to the beta fornl starts at once.…”
Section: Cocoa Butter-like Fatsmentioning
confidence: 99%